Chairman's report: African Elephant Specialist Group / Rapport du Presidente: Groupe des specialistes de l'elephant Africain - Holly Dublin (Pachyderm)
Clarifies the outfall of the two critical decisions made at the 10th Meeting of the Parties to CITES (COP10) affecting African elephants. The first mandated the transfer from Appendix I to II of the elephant populations of Botswana, Namibia and Zimbabwe. This downlisting signifies a clearer recognition that these countries do not meet the biological criteria for the maintenance of Appendix I. At the same time as downlisting the three populations provision was made for a one off sale of identified ivory stocks of known origin to Japan for 25.3 tonnes from Botswana, 13.8 tonnes from Namibia and 20.0 tonnes from Zimbabwe. Compliance will be judged by the standing committee, no export can take place for 18 months after the transfer to Appendix II (March 1999). The second decision allowed for a one off, non-commerial buyout of markded and registered government stocks in any range state. The decision provided for a 90 day period during which stocks were registered and marked by TRAFFIC, all were to be completed by 1997. Any proceeds from the non-commerical sale of registered stocks must be ploughed back into elephant related conservation projects through established funds dedicated to this purpose. The actual fate of the stocks was not specified, but resale is (at this time) prohibited.